Co-planting improves the phytoremediation efficiency of combined phenanthrene and copper co-contaminated soils. (1st January 2023) - Zhang, Ying; Li, Mingyue; Su, Aoxue; Lv, Xiaofei; Qiu, Yanling; Xu, Yan
Abstract: Co-contamination from both organic and inorganic pollutants is widely distributed in soils and is more difficult to remediate compared to single-type pollution. The co-planting pattern is an ideal phytoremediation strategy to remediate contaminated soils owing to their incomparable benefits originating from plant-plant interactions, but how to choose the best plant combinations and which factors affect the final remediating efficiency are still unclear. In this study, phytoremediation with different planting strategies of three herbaceous species, namely ryegrass ( Lolium perenne ), Dahurian wildrye ( Elymus dahuricus ), and Creeping bentgrass ( Agrostis stolonifera ), was conducted to remediate soils contaminated with both copper (Cu) and phenanthrene (PHE). The residual PHE content of all planting patterns was significantly lower compared to the unplanted bulk soil. More than 99% of total PHE losses were related to plant-stimulated microbial degradation, and plant intake was a minor pathway for PHE removal (accounting for less than 1%). The phytoextraction was the main Cu removal process by plants and the root uptake ability of Cu was the highest in Creeping bentgrass (an average of 708.9 mg kg −1 ) compared to the other two plants of ryegrass (an average of 269.9 mg kg −1 ) and Dahurian wildrye (an average of 268.0 mg kg −1 ). Two species co-planting combinations (ranging from an average of 264.4–302.3 mg m −2 ) greatly increased the total accumulated Cu content compared to single planting patterns (ranging from an average of 163.0–263.3 mg m −2 ). Combing the PHE removal results, the combination of Ryegrass x Creeping bentgrass, or Creeping bentgrass x Dahurian wildrye, where one species had a high biomass and the other species had a high uptake capacity, was a successful co-planting mode for the phytoremediation of multi-contaminated soils. Furthermore, microbes e.g. Massilia affiliated to Oxalobacteraceae, Sphingomonas affiliated to Sphingomonadaceae and Burkholderiaceae that can potentially degrade PAHs, as well as Rhizobium affiliated to Rhizobiaceae, Mucilaginibacter affiliated to Sphingobacteriaceae, and Caulobacter affiliated to Caulobacteraceae that can tolerate Cu stress were enriched in the rhizosphere. Overall, our study emphasizes the plant-plant interaction and the plant-microbe association, that both regulate phytoremediation effects on co-contaminated soils. Graphical abstract: Image 1 Highlights: Most of PHE losses were related to plant-stimulated microbial degradation. Two species co-planting combinations increased the total accumulated Cu content. Two plant species co-planting pattern was a successful phytoremediation strategy. Microbes that can degrade PAHs or improve plant resistance were enriched.